2020
DOI: 10.32598/rmm.8.2.893.1
|View full text |Cite
|
Sign up to set email alerts
|

Multi-drug Resistant Citrobacter freundii Isolates in a Burn Hospital in Northeast of Iran: A Single-Center Cross-sectional Study

Abstract: Background: Multi-drug resistant (MDR) Citrobacter freundii (C. freundii) as a causative agent of nosocomial infections is a health threat, especially in hospitals. This study was conducted to determine the prevalence of MDR C. freundii, considering isolation sites and a variety of utilized antibiotics. Materials and Methods: In this cross-sectional study, the clinical samples of C. freundii strains were collected and screened using traditional bacteriological tests in Zareh Hospital, Sari City, Iran, during 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…Plesiomonas shigelloides had significantly correlation with ARGs belonging to beta-lactam, chloramphenicol, multidrug resistance, etc., the same as Bacteroides fragilis , Escherichia-Shigella , Citrobacter , and Aeromonas . These were consistent with previous studies ( Ekundayo and Okoh, 2020 ; Norouzi Bazgir et al, 2020 ; Zhu et al, 2020 ; Li et al, 2021 ; Hassoubah, 2023 ). For instance, Ekundayo and Okoh (2020) have reported that Plesiomonas shigelloides in freshwater showed resistance to antibiotics and part of them had multi-resistance.…”
Section: Discussionsupporting
confidence: 94%
“…Plesiomonas shigelloides had significantly correlation with ARGs belonging to beta-lactam, chloramphenicol, multidrug resistance, etc., the same as Bacteroides fragilis , Escherichia-Shigella , Citrobacter , and Aeromonas . These were consistent with previous studies ( Ekundayo and Okoh, 2020 ; Norouzi Bazgir et al, 2020 ; Zhu et al, 2020 ; Li et al, 2021 ; Hassoubah, 2023 ). For instance, Ekundayo and Okoh (2020) have reported that Plesiomonas shigelloides in freshwater showed resistance to antibiotics and part of them had multi-resistance.…”
Section: Discussionsupporting
confidence: 94%